El espacio turístico de Chadefaud, un entrevero teórico: del historicismo al materialismo dialéctico y el sistemismo behaviourista - Callizo Soneiro, Javier (Geographicalia, 2017)
This paper is focused in the posthumous thesis work of Michel CHADEFAUD, in which he set forth his theory about turistic space. A marxist as well as a systemic-behaviourist model, even with some reminiscences taken from the best French historicism.